Phytochemical Analysis and Biological Activities of Zingiber officinale Grown in Different Geographical Regions of Nepal - Adhikari, Rajendra; Bhattarai, Keshab; Sharma, Khaga Raj (Amrit Research Journal, 2023)
Zingiber officinale, an important spice cash crop is an herbaceous perennial aromatic, medicinal plant that belongs to the family Zingiberaceae. Five samples of gingers were collected from Kaski (G1), Kanchanpur (G2), Makwanpur (G3), Sunsari (G4), and, Kathmandu (G5) districts. Ginger extracts were extracted by cold percolation method and essential oil was extracted by hydrodistillation using Clevenger apparatus. Ginger extract G4 showed the highest TPC (total phenolic content) of 140.91±2.93 mg GAE/g and G3 showed the lowest 43.31±6.80 mg GAE/g TPC value. Sample G5 showed the highest TFC (total flavonoid content) of 25.67 ± 1.16 mg QE/g and, G1 showed the lowest of 14.57±1.07 mg QE/g. DPPH (2,2-diphenyl-1-picrylhydrazyl) assay was used to determine the antioxidant activity of the ginger samples. The ginger sample G4 shows potent antioxidant activity with an IC50 of 162.73±3.22 μg/mL. The extract of sample G1 showed less radical scavenging activity with an IC50 value of 279.63±14.68 μg/mL. The essential oil of sample G5 shows potent antioxidant activity with an IC50 value of 68.98±7.24 μL/mL and, that of G4 showed less scavenging activity with an IC50 330.40±8.70 μL/mL. The diameter of the zone of inhibition (ZOI) produced by ginger extracts and essential oil on particular bacteria and fungi was measured for the estimation of their antimicrobial activity. Methanolic extracts and essential oils of ginger from all districts are ineffective against E. coli but displayed variable ZOI against Klebsiella pneumoniae, P. aeruginosa, S. aureus, and Salmonella typhi. Ginger extracts of all samples show a zone of inhibition in Candida ablicans, Candida parapsilosis, and Aspergillus flavus, but Fusarium oxysporum does not show any zone of inhibition. Essential oil has more antifungal activity than methanolic extracts. The LC50 value of the methanolic extract of sample G1 was found to be 1×105 μg/mL and the least from the methanolic extract of sample G2 with an LC50 value of 3.0×103 μg/mL, indicating that the methanolic extract of ginger was non-toxic.